Engaging Persons With Young Onset Dementia and Their Families in the Evaluation of Social Programs: Processes and Lessons Learned - Sarah E. Main; Paul Stolee; Samantha B. Meyer; Veronique M. Boscart (International Journal of Qualitative Methods)
There are few support services specifically for individuals living with young onset dementia (YOD) (age <65 years at diagnosis). To gain a better understanding of what individuals living with YOD desire in a day program, this project aimed to guide a collaborative re-development and evaluation of two new day programs in Southern Ontario. Using action research techniques and consultative processes, we worked with key stakeholder groups, alongside flexible and innovative methods, to engage individuals living with YOD, care partners, and staff. This project brings forward findings regarding processes to engage persons with YOD in research, beyond a biomedical framework (e.g., factors predicting institutionalization, the course and impact of neuropsychiatric symptoms), or focusing solely on information provided by family, care partners, or healthcare professionals. This article details two aims: 1) to document the research processes and approaches used to engage a range of participant groups, particularly younger persons with dementia, and describe the lessons learned, and 2) to provide reflections on the potential of Goal Attainment Scaling as an evaluation measure in the context of YOD programs.